Idiopathic Acquired Leukonychia in a 34-Year-Old Patient - Maria Rita Bongiorno; Mario Aricò (Case Reports in Medicine)
We present a rare case of a 34-year-old patient with persistent, progressive, acquired leukonychia totalis and partialis. Idiopathic acquired leukonychia is a rare chromatic disorder of the nail not associated with other abnormalities and discernible etiology. Our case report did not link the inheritance of leukonychia with diverse clinical syndromes. To our knowledge, only five cases of idiopathic, acquired, true total leukonychia were found in literature. This case was the sixth patient with asymptomatic idiopathic, white fingernails, and toenails without a hereditary cause.